2019
DOI: 10.3390/molecules24193447
|View full text |Cite
|
Sign up to set email alerts
|

Ayapana triplinervis Essential Oil and Its Main Component Thymohydroquinone Dimethyl Ether Inhibit Zika Virus at Doses Devoid of Toxicity in Zebrafish

Abstract: Zika virus (ZIKV) is an emerging mosquito-borne virus of medical concern. ZIKV infection may represent a serious disease, causing neonatal microcephaly and neurological disorders. Nowadays, there is no approved antiviral against ZIKV. Several indigenous or endemic medicinal plants from Mascarene archipelago in Indian Ocean have been found able to inhibit ZIKV infection. The purpose of our study was to determine whether essential oil (EO) from Reunion Island medicinal plant Ayapana triplinervis, whose thymohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…The study on the use of 2.5-dimethoxy-p-cymene has demonstrated that this molecule isolated from A. triplinervis EO is a potent inhibitor of ZIKV infection in human cells. Moreover, assessment of the biosafety of 2.5-dimethoxy-p-cymene extracted from A. triplinervis has shown that injection of this molecule in zebrafish does not lead to any signs of stress and does not affect fish survival, demonstrating the absence of acute toxicity of this compound [46]. However, different results were obtained by Unnikrishnan et al [45].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The study on the use of 2.5-dimethoxy-p-cymene has demonstrated that this molecule isolated from A. triplinervis EO is a potent inhibitor of ZIKV infection in human cells. Moreover, assessment of the biosafety of 2.5-dimethoxy-p-cymene extracted from A. triplinervis has shown that injection of this molecule in zebrafish does not lead to any signs of stress and does not affect fish survival, demonstrating the absence of acute toxicity of this compound [46]. However, different results were obtained by Unnikrishnan et al [45].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, EOs of Arnica flower heads from different European populations have shown their chemical polymorphism [8,9,15,18,21]. However, very interesting is the fact that the proportion of the main EO components from the Arnica rhizomes and roots, i.e., 2,5-dimethoxy-p-cymene and thymol methyl ether, is similar to the chemical oil profile in such species as Ayapana triplinervis [44][45][46].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results demonstrated that both EO and THQ inhibit ZIKV infection in human cells with IC 50 values of 38 and 45 μM. It was noted that the inoculation of THQ at the antiviral effective concentration does not lead to any stress and does not impact fish survival [ 54 ].…”
Section: Monoterpene Monocyclic Derivativesmentioning
confidence: 99%